Perencanaan Rest Area di Jalan Tol Kabupaten Probolinggo - Primasworo , Rifky Aldila (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
The highway is public roads that are part of the road network system and as national roads whose use is required to pay tolls. The Pasuruan – Probolinggo highway or Paspro is a 45 km long toll road connecting the Pasuruan area with Probolinggo. This research uses field survey or observation methods, Focus Group Discussion, primary and secondary case, and data analysis. According, plan the highway, it is necessary to plan a rest area according to the Regulation of the Minister of Public Works and Public Housing Number 10 / PRT / M / 2018. Rest and Service Area, hereinafter referred to as TIP, is a rest area equipped with various public facilities for toll road users, so that both drivers, passengers, and their vehicles can rest temporarily. The rest area in Probolinggo Regency consists of 2 points located at the locations, namely at Km 819 A and 819 B; km 833 A and 833 B. Rest areas for toll roads or TIP are included in category B with an area of ​​3 ha. Planning and Concepts of Rest Areas in Probolinggo Regency include rest areas as tourist destinations (has a beautiful view/scenic road), the rest area is also the transit area between modes of transportation, rest areas as logistics and toll roads that are integrated with industrial area.